Development of Transport Systems in Siberia and the Far East of Russia: Socio-Economic and Natural - Climatic Factors - TER-AKOPOV, Alexandr A.; BEZVERBNY, Vadim A. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.10.5(37).14, 2019)
The study is devoted to the development of the transport system of Siberia and the Far East of Russia. Renovation of railways, the laying of a new network of highways and the modernization of airports is the most important condition for the functioning of the state, its economic connectedness. Taking into account the territorial conditions of Russia – first of all, its length and spatial disproportionality – the problems of the transport and logistics infrastructure are of particular importance. The article describes the main trends in the development of the modern transport complex of Siberia and the Far East, identifies key problem areas of its operation and suggests practical measures to improve the development of transport infrastructure in the context of the tasks of spatial development of Russia. The findings of the study can be used both in strategic planning at the level of federal districts, and in further research at the national and interregional levels.